(untitled) (Global Journal of Human-Social Science, 2014)
Petrol scarcity is a malady and a serious economic problem in Nigeria. Successive governments have, often times, used it as a case for political advances, yet petrol scarcity remained an undefeatable macroeconomic monster in Nigeria. The need for petrol, its availability and affordability is obviously important especially as the risks and its attendant effects are undesirable, hence this investigation with focus on strategic management approaches for minimizing its occurrence. From the analysis, excessive corruption, mismanagement of government treasury, etc., were found as causes of petrol scarcity while socioeconomic unrest, hike in transport fare, retardation of economic growth, etc were found as its associated risks. Also government strategies of task force formation, downstream sector reforms, etc were found to have no significant mitigating effect on petrol scarcity. Consequently, the use of balanced score card, SWOT analyses etc were recommended as potent strategic approaches for managing and forestalling petrol scarcity in Nigeria.